A violência sexual na infância: uma leitura psicanalítica sobre o corpo - Pohl, Katherine (2018)
This study aimed to analyze the body as a locus of expression of the psychic suffering after undergoing a traumatic experience such as incestuous sexual violence in childhood. Psychoanalysis was the theoretical and methodological approach of the research. The investigative path was laid out from the construction of a clinical case. Lis, eighteen years old, was referred to psychological counseling after reporting physical, psychological and sexual violence against her biological father. The consultations lasted for two years and the narrative of the case was based on the reading of the analyst-researcher's reports. The body dimension emerged as a privileged aspect of the analysis, with specific symptomatic formations that involved compulsive eating, self-harm and sleepwalking, among others. The analysis of the case signaled that the body manifestations anchored marks of the traumatic drive excess and that the body appeared as the stage for primitive experiences. Faced with Lis's significant difficulty in discriminating, organizing and welcoming her affections and experiences, the body became the main channel of communication between analyst and analysand. By means of the perceptive sensitivity to the gestures and expressive movements of the body of Lis, the representation of the manifestations of the body and the reception of the impact of the pulsional forces could gradually be constructed. New meanings for the untouched contents could be developed and a containment psychic condition could begin to set in. Thusly, the research pointed to the inseparability between the analytical field and the problematic of the body, a witness of the unsaid and of what escapes the subject's symbolic discourse.